All‐in‐One: Multifunctional Hydrogel Accelerates Oxidative Diabetic Wound Healing through Timed‐Release of Exosome and Fibroblast Growth Factor. Issue 1 (17th November 2021) - Xiong, Yuan; Chen, Lang; Liu, Pei; Yu, Tao; Lin, Chuanchuan; Yan, Chenchen; Hu, Yiqiang; Zhou, Wu; Sun, Yun; Panayi, Adriana C.; Cao, Faqi; Xue, Hang; et al.
Abstract: The treatment of diabetic wounds remains a major challenge in clinical practice, with chronic wounds characterized by multiple drug‐resistant bacterial infections, angiopathy, and oxidative damage to the microenvironment. Herein, a novel in situ injectable HA@MnO2 /FGF‐2/Exos hydrogel is introduced for improving diabetic wound healing. Through a simple local injection, this hydrogel is able to form a protective barrier covering the wound, providing rapid hemostasis and long‐term antibacterial protection. The MnO2 /ε‐PL nanosheet is able to catalyze the excess H2 O2 produced in the wound, converting it to O2, thus not only eliminating the harmful effects of H2 O2 but also providing O2 for wound healing. Moreover, the release of M2‐derived Exosomes (M2 Exos) and FGF‐2 growth factor stimulates angiogenesis and epithelization, respectively. These in vivo and in vitro results demonstrate accelerated healing of diabetic wounds with the use of the HA@MnO2 /FGF‐2/Exos hydrogel, presenting a viable strategy for chronic diabetic wound repair. Abstract : Using a convenient mixed injection, an HA@MnO2 /FGF‐2/Exos hydrogel dressing covering the diabetic wound tightly can be rapidly formed. The positive quaternary ammonium groups in the graft play a long‐term antibacterial role. The MnO2 /e‐PL nanosheet acts as a nanoenzyme to catalyze the conversion from H2 O2 to O2 . The released Exos M2@miR‐223 simulate long‐lasting angiogenesis and the released FGF‐2 accelerates epithelization efficiently.